Synthesis of Spherical Fluorine Modified Gradient Li-Ion Battery Cathode Material LiNi0.80Co0.15Al0.05O2 by Simple Solid Phase Method. Issue 5 (1st January 2018) - Xia, Shubiao; Li, Fushao; Cheng, Feixiang; Li, Xue; Sun, Chengke; Liu, Jian-Jun; Hong, Guo
Abstract : The high nickel layer cathode LiNi0.80 Co0.15 Al0.05 O2 (NCA) has excellent discharge capacity and better cycling performance. However, the NCA cathode still has the following disadvantages such as harsh synthesis conditions, cation mixing and poor thermal stability. A spherical fluorine modified gradient NCA is successfully prepared by a simple solid phase method. The F-modification NCA has a good spherical shape which shows a gradient distribution with high surface F and Al contents, and high nickel content in the core. XRD results reveal that F-modification NCA sample has well-ordered layer structure. However, there is a slight decrease in the cell parameters and interlayer spacing with the F doping into the NCA crystal lattice, due to the small F − radius and the largest electronegativity. Energy Dispersive X-Ray Spectroscopy (EDX) analysis reveals that fluorine ions are successfully substituted in the lattice. The cycling stability of the F-modification NCA samples are enhanced, especially at high rates. At 2C rate, the initial discharge specific capacity is 142.34 mAh g −1, and compared with that of 107.73 mAh g −1 after 200 cycles, the capacity losses only 24%. Electrochemical impedance spectroscopy (EIS) further indicates that F-modification could help inhibit the increasing of polarization and change the kinetics of NCA cathode.